Demographic Variables and Adolescents’ Science Academic Engagement in Ibadan, Nigeria - Oludele Olagoke Ogunlade; Olufemi Akinloye Bolaji (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
The low academic engagement of students in science education is a significant concern as it can affect learning achievement and interest in the discipline. Demographic factors are believed to influence the level of academic engagement in science among adolescents. This study aims to analyze in depth the impact of family structure and school type on adolescents' academic engagement in science. This is a quantitative study with a comparative design. The subjects of the study consisted of 227 adolescents selected through simple random sampling. The instrument used was a structured questionnaire that included scales for academic self-efficacy in science, academic engagement motivation in science, and demographic data (gender, age, religion, family structure, and parental education qualifications). Data were collected through the distribution of questionnaires and analyzed using descriptive statistics (percentage, frequency, mean, and standard deviation) as well as t-tests. The results showed significant differences in academic engagement in science based on family structure and school type. However, no significant differences were found based on gender, age, religion, or parental education qualifications. The conclusion of this study emphasizes the importance of considering family environment and school institution factors in enhancing adolescents' academic engagement in science. The implication is that all parties, including parents and educational institutions, need to create an environment that supports student engagement in science.